NONLINEAR VIBRATIONS OF FLUID-FILLED VISCOELASTIC CYLINDRICAL SHELLS (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
In this work the non-linear vibrations of a simply supported viscoelastic fluid-filled circular cylindrical shells subjected to lateral harmonic load is studied. Donnell's non-linear shallow shell theory is used to model the shell, assumed to be made of a Kelvin-Voigt material type, and a modal solution with six degrees of freedom is used to describe the lateral displacements. The Galerkin method is applied to derive a set of coupled non-linear ordinary differential equations of motion. The influence of shell geometry, flow velocity and dissipation parameter are studied and special attention is given to resonance curves. Obtained results show that the viscoelastic dissipation parameter, flow velocity and geometry have significant influence on the nonlinear behavior of the shells as displayed in instability loads and resonance curves.